Effects of initial glucose concentration on fermentation performance of Kluyveromyces marxianus cells immobilized on banana leaf sheath pieces - Hoang Du Le" (Science Faculty of Chiang Mai University, 2019)
Ethanol fermentation was carried out by Kluyveromyces marxianus cells immobilized on banana leaf sheath pieces at different initial glucose concentrations (120, 160, 200, 240 and 280 g.L-1). Fermentation performance of the free yeast was also evaluated and compared. Increase in glucose concentration from 120 to 200 g.L-1 did not affect the growth and ethanol formation of both immobilized and free yeast. In the glucose concentration ranging from 200 - 280 g.L-1, the growth and ethanol formation of both immobilized and free yeast decreased. The immobilized yeast demonstrated faster sugar assimilation and higher final ethanol concentration in comparison to the free yeast at all glucose concentrations. The maximum ethanol concentration produced by the immobilized yeast was 1.12 to 1.67 times higher than that produced by the free yeast as the glucose concentration increased from 120 to 280 g.L-1.